Restrictions on business mobility : a study in political rhetoric and economic reality - McKenzie, Richard B. (Washington : American Enterprise Institute for Public Policy Research, 1979)
The text examines proposals to restrict the interregional movement of businesses, especially from the northern Snowbelt to the southern sunbelt.
Includes bibliographical references.
osa 06/07/2017
Loans
Keywords: Industrial location; Business relocation; Industrial policy